VD_FINDINFO ML / 2015 / 180 vom 3. September 2015 - VD Tribunal cantonal (2015)
DÉPENS, FICTION DE LA NOTIFICATION | 106 al. 1 CPC (CH), 138 al. 3 let. a CPC (CH), 138 CPC (CH), 95 al. 1 let. b CPC (CH), 95 CPC (CH)